Sharia Compliance and Islamic Digital Banking: Empowering SMEs in Indonesia - Supriyono, Supriyono; Terminanto, Ade Ananto; Mulazid, Ade Sofyan; Suherlan, Ade (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study investigates how Sharia compliance and trust shape SMEs' adoption behavior using an extended Unified Theory of Acceptance and Use of Technology (UTAUT 3) framework. The rapid digital transformation of the banking sector necessitates deeper insights into the factors driving the adoption of Islamic digital banking, particularly among Small and Medium Enterprises (SMEs) in Indonesia. Through a quantitative approach employing an online survey of 129 SME respondents, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that Sharia compliance significantly influences actual usage but does not moderate the relationship between behavioral intention and adoption. Trust and personal innovation emerge as key determinants of SMEs' adoption, while facilitating conditions, hedonic motivation, and price value demonstrate negligible effects. These insights underscore the necessity for Islamic banks to effectively integrate Sharia principles into their digital banking services to foster greater trust and engagement among SMEs. This study contributes to the literature by expanding the UTAUT 3 framework within Islamic finance and digital banking contexts, offering practical recommendations for Islamic financial institutions to enhance service accessibility and customer trust. Future research should examine longitudinal trends and explore a broader demographic and institutional spectrum to validate these findings and assess the evolving landscape of Islamic digital banking.